A Self‐Assembled Small‐Molecule‐Based Hole‐Transporting Material for Inverted Perovskite Solar Cells. Issue 45 (1st July 2020) - Más‐Montoya, Miriam; Gómez, Paula; Curiel, David; da Silva, Ivan; Wang, Junke; Janssen, René A. J.
Abstract: Hybrid organic–inorganic perovskite solar cells have recently emerged as one of the most promising low‐cost photovoltaic technologies. The remarkable progress of perovskite photovoltaics is closely related to advances in interfacial engineering and development of charge selective interlayers. Herein, we present the synthesis and characterization of a fused azapolyheteroaromatic small molecule, namely anthradi‐7‐azaindole (ADAI ), with outstanding performance as a hole‐transporting layer in perovskite solar cells with inverted architecture. Its molecular arrangement, induced by hydrogen‐bond‐directed self‐assembly, favors a suitable morphology of the perovskite layer, reducing the effects of recombination as revealed by light intensity dependence, photoluminescence, and electroluminescence studies. Abstract : Fused‐ring systems : A fused azapolyheteroaromatic derivative self‐assembles into an efficient hole‐transporting material for perovskite solar cells with an inverted planar architecture (see figure).